Cost-effective sustainable-engineering of CH3NH3PbI3 perovskite solar cells through slicing and restacking of 2D layers. (June 2017) - Wu, Congcong; Li, Haijin; Yan, Yongke; Chi, Bo; Pu, Jian; Li, Jian; Sanghadasa, Mohan; Priya, Shashank
Abstract: Owing to their high conversion efficiency and potentially cost-effective manufacturing, organic–inorganic lead halide perovskite solar cells (PSCs) have been dominant photovoltaic research topic in this decade. The photovoltaic performance of PSCs is highly dependent upon the quality of perovskite layer. In order to advance the deployment of PSCs, fabrication of high-quality perovskite film using a facile and sustainable process is essential. This study provides significant breakthrough in this direction. A novel fabrication process is demonstrated that allows slicing of 2D layers from single crystals and restacking them to fabricate high-quality perovskite film. The discovery that CH3 NH2 can slice the 3D CH3 NH3 PbI3 perovskite crystal into 2D layered perovskite intermediates via intercalation process opens a new pathway for pursuing synthesis of a variety of photovoltaic materials. The 2D layered intermediate shows high solubility in acetonitrile (ACN) solvent, which is considered as a replacement for N, N-dimethylformamide (DMF) in order to enable sustainable processing. This solvent system enables fabrication of high-quality perovskite layer by one-step synthesis method. Based on this cost-effective sustainable synthesis approach, low temperature processed PSC was found to match the performance of PSC synthesized using high temperature process. Graphical abstract: Highlights: High quality, excellent crystallinity CH3 NH3 PbI3 perovskite film was synthesized through slicing and restacking single crystal. The process enables a sustainable solvent utilization and facile one-step deposition method. Reveal an in-situ fabrication of 2D layered perovskite through intercalation.